Dampak Perkembangan Ekonomi Digital terhadap Pertumbuhan Sektor E-commerce di Indonesia: Perspektif Teknologi, Konsumen, dan Regulasi - Lubis, Nurliza; Ainul Yusna Harahap; Rahmad Tantawi; Nuri Aslami; Tina Novianti Sitanggang (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This study examines the impact of digital economic development on the growth of the e-commerce sector in Indonesia, focusing on the roles of digital technology, consumer behavior, and government regulation. Based on data from Google, Temasek, and Bain & Company (2023), Indonesia's e-commerce transaction value increased significantly from USD 21 billion in 2019 to USD 77 billion in 2022, contributing 8.9% to GDP in 2023. Using a quantitative method and surveys of 150 respondents consisting of e-commerce companies and consumers, multiple regression analysis results indicate that consumer behavior has the greatest influence (β = 0.467; p < 0.05), followed by digital technology (β = 0.325; p < 0.05) and government regulation (β = 0.178; p < 0.05). The model explains 73.2% of the variability in e-commerce growth, with the remaining 26.8% influenced by other external factors. This study has limitations regarding the sample size, focus on specific variables, and reliance on quantitative methods. Future researchers are advised to broaden the scope of the study, consider additional relevant variables, and employ more diverse approaches to obtain more comprehensive results. This study highlights the need for collaboration among governments, businesses, and consumers to create an inclusive and sustainable e-commerce ecosystem.